Anthropomorphism of God elicits beliefs in tempting fate - Chua, Felicia Sui Jin (Nanyang Technological University, 2020)
Why are people reluctant to celebrate a job offer in advance or leave a slow checkout line for another one? Such actions, exhibiting beliefs in tempting fate, were examined through a proposed account of anthropomorphism of God, which describes the tendency to imbue a supernatural agent with human-like mental capacities. The key assumption underlying the belief in tempting fate is the perception that a supernatural agent, God or not, has a mind sophisticated enough to understand intentions and punish in an ironic manner. These processes are less applicable to a non-anthropomorphic God that is perceived as abstract and impersonal. This line of logic predicts that the priming of a highly anthropomorphic view of God should elicit a strong belief in tempting fate. As predicted, experimental analyses on a community sample of American participants showed that those who were primed with a highly (vs. lowly) anthropomorphic view of God perceived God as more capable of moderating worldly affairs. In addition, participants primed with a highly (vs. lowly) anthropomorphic view of God tended to have a stronger belief in tempting fate, this effect was especially significant for Christian participants. These results show that the existence of beliefs in tempting fate, which manifests in many different forms, can be explained by the anthropomorphism of God.